Electron impact ionisation and other molecular processes for organoplatinum compounds. (3rd June 2022) - Bhavsar, Rakesh; Thakar, Yogesh; Vinodkumar, Minaxi; Limbachiya, Chetan
Abstract : Electron interactions with platinum-based chemotherapeutic organoplatinum compounds, cisplatin (H6 N2 Cl2 Pt), nedaplatin (C2 H8 N2 O3 Pt), carboplatin (C6 H12 N2 O4 Pt) and oxaliplatin (C8 H14 N2 O4 Pt), are studied for ionisation and other molecular processes from ionisation potential (IP) to 5 keV. Elastic cross sections Q el, inelastic cross sections Q inel and total cross sections Q T are computed using Spherical Complex Optical Potential (SCOP) formalism and ionisation cross-sections Q ion and summed excitation cross sections ∑ Q exc are derived through Complex Scattering Potential – ionisation contribution (CSP-ic) method. Only theoretical data is available in the literature for these molecules and we find good accord with them. This is the first report of Q T, Q inel and Q exc for all these molecules and Q el for Nedaplatin. GRAPHICAL ABSTRACT: UF0001